Sufism Scholars Network in the Middle East, India, and Indonesia - Dwi Afrianti (International Journal of Nusantara Islam, 2016)
The history of Islam in Indonesia cannot be separated from the affected of local culture, religion, belief earlier, and culture of the spreader of Islam which are also influenced by religion and beliefs held previously, as well as the entry period into certain areas of different life times, willingness to form the teachings of the scholars/king. All of this shows the complexity of the uniqueness of Islam in Indonesian as the majority religion among diverse religions in Indonesia. Sufism are directly involved in the spread of Islam in Indonesia with a unique teaching that facilitate the engaging of non-Muslim communities into Islam, compromise or blends Islam with religious and beliefs practices rather than local beliefs change from an international network to the local level. The terms and the elements of the pre-Islamic culture are used to explain Islam itself. Islamic history of Sundanese, there is a link in teachings of Wihdat al-Wujud of Ibn al-‘Arabi who Sufism Scholar that connected between the international Islamic networks scholars and Sundanese in Indonesia. It is more popular, especially in the congregation of Thariqat Syattariyah originated from India, and it is widespread in Indonesia such as Aceh, Minangkabau and also Pamijahan-Tasikmalaya that brought by Abdul Muhyi since 17th century ago.